What ignorance could not be - Ekaterina Kubyshkina; Mattia Petrolo (Principia: An International Journal of Epistemology, 2020)
In the current debate there are two epistemological approaches to the definition of ignorance. The Standard View defines ignorance simply as not knowing, while the New View defines it as the absence of true belief. We argue that both views provide necessary, but not sufficient conditions for ignorance, and thus do not constitute satisfactory definitions for such a notion.